2013
DOI: 10.4155/fmc.13.130
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Strategies Impacting Cancer Cell Glutamine Metabolism

Abstract: The metabolic adaptations that support oncogenic growth can also render cancer cells dependent on certain nutrients. Along with the Warburg effect, increased utilization of glutamine is one of the metabolic hallmarks of the transformed state. Glutamine catabolism is positively regulated by multiple oncogenic signals, including those transmitted by the Rho family of GTPases and by c-Myc. The recent identification of mechanistically distinct inhibitors of glutaminase, which can selectively block cellular transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 122 publications
4
106
0
Order By: Relevance
“…The role of kidney-type glutaminase in cancer has been heavily investigated [7,[71][72][73][74][75][76][77]. The Cancer Genome Atlas (TCGA) pan-cancer gene expression data show high expression of GLS in acute myeloid leukemia, adrenocortical cancer, triple-negative breast cancer, colorectal cancer, kidney clear or papillary cell carcinoma, lung adenocarcinoma, melanoma, mesothelioma, pancreatic cancer, sarcoma and thyroid cancer [78,79].…”
Section: Kidney-type Glutaminase: Implications In Cancermentioning
confidence: 99%
“…The role of kidney-type glutaminase in cancer has been heavily investigated [7,[71][72][73][74][75][76][77]. The Cancer Genome Atlas (TCGA) pan-cancer gene expression data show high expression of GLS in acute myeloid leukemia, adrenocortical cancer, triple-negative breast cancer, colorectal cancer, kidney clear or papillary cell carcinoma, lung adenocarcinoma, melanoma, mesothelioma, pancreatic cancer, sarcoma and thyroid cancer [78,79].…”
Section: Kidney-type Glutaminase: Implications In Cancermentioning
confidence: 99%
“…Recent studies confirmed that SIRT4 indeed acts as a tumor suppressor, by repressing glutamine metabolism and promoting genomic stability (30,69,71). Glutamine is a key amino acid required for diverse intracellular processes such as macromolecular synthesis, redox homeostasis, oxidative metabolism, and many others (95). Although most mammalian cells can synthesize glutamine, under conditions of rapid cell proliferation, such as cancer, a steady extracellular source of glutamine becomes essential.…”
Section: Sirt4 Acts As a Tumor Suppressor Via Repression Of Glutaminementioning
confidence: 99%
“…Glutamine is initially hydrolyzed by glutamate synthase (GLS) to glutamate, which is then subsequently converted to a Krebs cycle intermediate, a-ketoglutarate, by the action of GDH (95). SIRT4 interacts with GDH in pancreatic b-cells and ADP-ribosylates GDH to repress its activity (52).…”
Section: Sirt4 Suppresses Glutamate Dehydrogenase Activitymentioning
confidence: 99%
“…17 However, activity in patients with recurrent malignant glioma was low. 18 More recently, therapeutic approaches targeting amino acid transport were suggested including for example inhibition of the glutamine transporter SLC1A5 15 and inhibition of the glutamate-cystine antiporter xCT. 19 Much of the renewed interest in therapeutically targeting of glutamine metabolism is related to the first step of glutamine utilization, the conversion of glutamine to glutamate by the enzyme glutaminase.…”
mentioning
confidence: 99%
“…21 Properties of the new glutaminase inhibitors are extensively reviewed in the recent literature. 15,22 Both agents specifically inhibit the GLS isoenzyme (both splice variants KGA and GAC) and act by allosteric binding to the protein.…”
mentioning
confidence: 99%